Recueil de textes concernant l'histoire du Soudan - Archinard, Louis, 1850-1932
Compilation of texts concerning the history of pre-colonial French Sudan (i.e. Mali), forming part of the Fonds Archinard in the Bibliothèque nationale, Département des manuscrits: Taraifa, by Sidi Moukhtar, concerning the populations of the Sahara; treatise written by Ahmad Baba Al-Toumboukti concerning Sudan; significant fragments concerning the history of Tombouctou in second half of the 18th century, attributed to Maula Ghassouni; fragments of Fatassi, written by Mahmadou Koti; a letter of Sheikh Moukhtar; a legal consultation written by Mohyi ad-Din Abd Allah Sidi Mohammad ibn Abd Al-Karim Al-Mogali Al-Tilimsani; a list of the kings of Massina; a historical treatise by Ahmad Al-Bika; a fragment of Fatassi; a letter of Abd Al-Kadir, general of Sheikh Ahmadou, concerning a campaign against the Tauregs; le Divan al-loulouk fi salatin al-Soudan, a history of Sudan from 1656 to 1747; le Tohfat al-albab, by Abou Abd Allah Al-Gharnati.